Kualitas Climate Reporting Disclosure Perusahaan Multinasional di Dua Sektor Periode 2020-2023 - Hiung, Steven Jenius Bun Fie; Meiden, Carmel (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2023)
Abstract Climate change is a global problem that is the responsibility of every company that contributes to carbon emissions. The Task Force on Climate Related Financial Disclosure is a recommendation in disclosing climate reporting disclosures. This study aims to detemine the quality of company climate reporting disclosures. This study uses a descriptive study design with content analysis method. The objects of research are 5 multinational companies in the banking industry sector and 5 multinational companies in the oil and gas industry sector which issue climate-related disclosures for the 2020-2022 period. The results of the analysis state that the quality of climate disclosure in corporate reporting based on TCFD recommendations has no consistency because the scores obtained still go up and down irregularly. In addition, the quality of corporate climate reporting disclosures in the banking industry sector is better than the oil and gas industry sector. The conclusion of this study states that the quality of climate disclosure in corporate reporting is still not optimal in the disclosure process. This is because the standard is still new and is still under development. Abstrak Perubahan iklim merupakan permasalahan global yang menjadi tanggung jawab setiap perusahaan yang memberikan sumbangan emisi karbon. Task Force on Climate Related Financial Disclosure merupakan rekomendasi dalam pengungkapan climate reporting disclosure. Tujuan penelitian ini untuk menilai kualitas climate reporting disclosure perusahaan. Penelitian ini mengunakan desain studi deskriptif dengan metode content analysis. Objek penelitian adalah 5 perusahaan multinasional di sektor industri perbankan serta 5 perusahaan multinasional di sektor industri minyak dan gas yang menerbitkan climate related disclosure untuk periode 2020-2022. Hasil analisis menyatakan bahwa kualitas climate reporting disclosure perusahaan atas rekomendasi TCFD tidak memiliki konsistensi karena skor yang didapat masih naik dan turun secara tidak teratur. Selain itu kualitas climate reporting disclosure perusahaan sektor industri perbankan lebih baik dibandingkan sektor industri minyak dan gas. Kesimpulan dari penelitian ini menyatakan bahwa kualitas climate reporting disclosure perusahaan masih tidak maksimal dalam proses pengungkapan. Disebabkan karena standar yang masih baru dan masih dalam tahap perkembangan.